High triplet energy exciplex hosts for deep blue phosphorescent organic light-emitting diodes. Issue 24 (1st June 2017) - Song, Wook; Lee, Ha Lim; Lee, Jun Yeob
Abstract : High triplet energy exciplex hosts for deep blue phosphorescent organic light-emitting diodes were developed by synthesizing a high triplet energy hole transport type host material designed for exciplex formation with a high triplet energy electron transport type host material derived from a diphenyltriazine. Abstract : High triplet energy exciplex hosts for deep blue phosphorescent organic light-emitting diodes were developed by synthesizing a high triplet energy hole transport type host material designed for exciplex formation with a high triplet energy electron transport type host material derived from a diphenyltriazine. The highest occupied molecular orbital level of the hole transport type host materials was precisely controlled to manage the exciplex formation with the electron transport type host. Two exciplex hosts with high triplet energies of 2.94 and 2.95 eV were demonstrated using the synthesized hole transport type hosts and they were effective as the hosts of a deep blue triplet emitter.